Surf Fishing Prospect: Developing Pangandaran Beach Tourism Destination - Dicky Arsyul Salam; Beta Budisetyorini; Deddy Adisudharma; Wisi Wulandari; Mega Fitriani Adiwarna Prawira (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
Fishing tourism has become a global recreational trend, providing visitors with a memorable beach activity-based experience. Fishing tourism is a relatively new development in sustainable tourism, where tourists can participate in fishing operations by using surf fishing techniques to catch and cook freshly caught fish on-site. Pangandaran beach tourism destination provides a potential spot for surf fishing. This research examines the prospects for developing surf fishing to increase quality beach activity experiences in Pangandaran. This is achieved through face-to-face interviews with five experienced fishers and ten tourists who wanted to participate in this process. By using ansoff matrix analysis, the surf fishing prospect of Pangandaran Beach tourism destination suggests implementing a product development strategy to create new products of fishing tourism experiences and techniques provided for the existing tourist market fishing lover.